Saikosaponin-d Suppresses COX2 Through p-STAT3/C/EBPβ Signaling Pathway in Liver Cancer: A Novel Mechanism of Action - Ren, Mudan; McGowan, Eileen; Li, Yarui; Zhu, Xiaofeng; Lu, Xinlan; Zhu, Zhanfang; Lin, Yiguang; He, Shuixiang (Frontiers in Pharmacology, 2019)
Saikosaponin d (SSd) is the active extract from Radix Bupleuri, the dried root from the plant Bupleurum falcatum, which has been used to treatment liver disease in China for thousands of years. It has been shown that SSd possess various valuable pharmacological activities including anticancer, anti-inflammatory effects. However, the mechanism underlying the anti-cancer activity of SSd is still largely unknown. Here we explore the potential mechanism of SSd as an anti-cancer treatment for liver cancer. Human hepatocellular carcinoma cell lines, SMMC-7721 and HepG2, were used to study the effect of SSd in liver cancer. Using the MTT and annexin-V-FITC/PI assays, Western blots, immunohistochemistry, qRT-PCR and the JAK2 specific-inhibitor AG490, we explored the p-STAT3/C/EBPβ/COX-2 signaling pathway. We found that SSd effects anti-tumorigenicity through cyclooxygenase (COX)-2 suppression in liver cancer cells via the p-STAT3/C/EBPβ signaling pathway. SSd effectively inhibited cell proliferation in a dose-dependent manner. Apoptosis was significantly increased in cells treated with SSd (2.5 µg/ml-15 µg/ml) with concurrent increase and decrease in pro-and anti-apoptosis proteins respectively. COX-2, C/EBPβ, and p-STAT3 was significantly decreased, at both translational and transcriptional levels, by SSd in a dose-dependent fashion. AG490 produced similar inhibitory effects on STAT3, p-STAT3, C/EBPβ and COX-2. Conclusion: Our data suggests that SSd controls liver cancer proliferation through suppression of the p-STAT3/C/EBPβ signaling pathway and inhibiting COX2 expression. These findings further our understanding of the pharmacological action of SSd providing new information on SSd mechanism of action and supporting SSd as a novel therapy for liver cancer.